Analisis Stilistika Ungkapan Pantang Larang Masyarakat Melayu di Desa Sungai Nibung Kecamatan Siak Kecil Kabupaten Bengkalis - Rani, Sarimah; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The expression abstinence is a prohibition that will befall someone if they do it. The words used in tabang hara are usually related to frightening things, such as in the form of disease, disaster and the supernatural. The problems in this research are 1) What is the meaning of the connotation contained in the expression abstinence and prohibition in the people of Sungai Nibung Village, Siak Kecil District, Bengkalis Regency?, 2) What is the diction contained in the expression abstinence and prohibition in the people of Sungai Nibung Village, Siak Kecil District, Bengkalis Regency? This research aims to find out the meaning of a person's expression which is conveyed indirectly by giving advice using connotation meaning and word choice. The method the author uses is a descriptive ethnographic method. The theories used in this research are the theories of Nurgiyantoro (2013), Chaer (2012), Keraf (1948), and Tarigan (2019). Data collection techniques were carried out using observation, interviews and documentation techniques. The results of this research show that there are 5 data regarding the expressions of abstinence and prohibition in Sungai Nibung Village, Siak Kecil District, Bengkalis Regency related to the connotative meaning aspect and 8 data regarding the diction aspect.